ANSWERS: 2
  • Ok here we go 1/(x-2) +3 =-16/x^2+x-6 =>3x-6+1/x-2=-16/x^2+x-6 =>3x-5/x-2=-16/x^2+3x-2x-6 =>3x-5/x-2=-16/(x-2)(x+3) =>3x-5=-16/x+3 =>3x^2-5x+9x-15=-16 =>3x^2+4x+1=0 =>3x^2+3x+x+1=0 =>(3x+1)+(x+1)=0 =>x=-1/3 or x=-1 Come back to me if you don't understand any step.
  • (1/x-2)+3=(-16/x^2+x-6) (1/x-2)+3=-16/(x+3)(x-2) (1/x-2)+3(x-2)/(x-2)=-16/(x+3)(x-2) 1+3(x-2)=-16/(x+3) (1+3x-6)(x+3)=-16 (3x-5)(x+3)=-16 3x^2+4x-15=-16 3x^2+4x+1=0 (3x+1)(x+1)=0 x=-1/3, x=-1

Copyright 2018, Wired Ivy, LLC

Answerbag | Terms of Service | Privacy Policy